Dignified care and associated factors among mothers who gave birth at public hospitals, in Sidama Regional State, southern Ethiopia, 2023 - Worku Getachew; Tebeje Ashegu; Muluken Demeke; Rekiku Fikre (BMC Women's Health)
Abstract Background Dignified care is an important priority for childbearing mothers. Threats to this deteriorate the therapeutic relationship between healthcare providers and clients, which leads to a negative effect on the quality of care. However, little evidence is identified about dignified care and associated factors in the Ethiopian context. Therefore, this study aimed to assess dignified care and associated factors among mothers who gave birth at public hospitals in Sidama Regional States, southern Ethiopia, 2023. Method An institution-based cross-sectional study was conducted among 418 mothers who gave birth at public hospitals in Sidama Regional States from July 30 to August 30, 2023. A systematic random sampling technique was employed to select study participants. An interviewer-administered structured questionnaire was used, and the data was collected by Kobotool and analyzed using SPSS Version 25. Bivariable and multivariable logistic regression analyses were conducted, and the crude and adjusted odds ratios, together with their corresponding 95% confidence, were computed. A P value < 0.05 was considered a level of statistical significance in this study. Results In this study, the overall study participants’ magnitude of dignified care was found to be 44.1%. Secondary education (AOR: 3.91, 95% CI: 1.56, 9.82), spontaneous vaginal delivery (AOR: 2.68, 95% CI: 1.31, 5.46), the presence of a companion during labor and delivery (AOR: 12.35, 95% CI : 7.08, 21.53), and less than two days hospital stay (AOR: 3.26, 95% CI: 1.37, 7.75), and midwife attendance of labour and delivery (AOR = 4.47 (1.40–14.25) were significantly associated with dignified care. Conclusions The findings of this study showed that the dignified care of mothers who gave birth at public hospitals in Sidama Regional State was relatively low to the pooled prevalence of respectful maternity care in Ethiopia. In light of these results, it is recommended to prioritize midwife attendance during labor and delivery, promote the presence of companions, facilitate a shorter hospital stay, and enhance educational opportunities.